The ex post analysis and perspectives of an Urban Creativity program between artistic requalification and social regeneration - Scardapane, Silvia; Mongelli, Monica (Street Art & Urban Creativity, 2022)
In 2015 INWARD - National Observatory on Urban Creativity started the project “Parco dei Murales”, a process of artistic requalification and social regeneration in the Ponticelli district, the eastern part of the great city of Naples. Four years after the completion of the pictorial works, questions regarding the influence of the creative program on the urban area arise: how did these interventions generate a change in the neighborhood? What impact did they have had on the community? Many inhabitants perceive the eastern outskirts of Naples as a marginal space of the metropolis of Southern Italy, a “liminal” area not only geographically but also socially if we think about the exposure of some segments of the population to situations of the uncertainty of the social and economic condition. It is noted that this area manifests an evident lack of services that can allow a transformation towards a condition of certainty. The artistic and social experience in the “Parco dei Murales”, was born to subvert all this and allow the external public to enter an inhabited space previously considered repulsive. In relation to three macro-categories as Art, Social, and Promotion, we will try to answer the initial questions to investigate the positive and negative aspects of a collective program. Through data related to the work experience collected from 2015 to 2021, to the elaboration of surveys, outputs submitted to the community, and comparisons with similar realities in Italy, we have reached a liminal moment of the work that is a moment of waiting between what has been achieved and the transformation in progress. What are future evolutions? How to envisage the extension of an urban creativity program for the social in a creative territorial system?